PROTOTYPE PENYARING ASAP ROKOK PADA SMOKING AREA MENGGUNAKAN PULSE WIDTH MODULATION (PWM) DAN FUZZY TSUKAMOTO - Vega Nataya Kinanti; Muh. Yamin; LM. Fid Aksara (Informatics Engineering Department of Halu Oleo University, 2016)
Smoking is an activity that can damage not only the smokers but also the people around them.The main purpose of making this tool is to put up freshness air and lift a hand for both the smokersand the secondhand smokers in a same room. Pulse Width Modulation (PWM) and Fuzzy Logic byTsukamoto’s method are used in process of making this tool. This tool is designed to control toxic gases from the tobacco smoke by expediting the air circulation in the room. This tobacco smoke filterworks by taking the tobacco smoke outside. The input from this system is MQ2 sensor which detects tobacco smoke and MQ7 sensor that can detect the carbon monoxide then the input result of both sensors will be processing in a microcontroller. Afterwards, microcontroller commands to activate the disposal fan. Hence, this tool is expected can be used by the society and government to control thetoxic gases caused by the tobacco smoke in public areas especially can be used in smoking areas. Keywords— Smoke, Microcontroller, PWM, Fuzzy Tsukamoto, Sensor.